Web information systems and technologies : International Conferences, WEBIST 2005 and WEBIST 2006 : revised selected papers - International Conference on Web Information Systems and Technologies (1st : 2005 : Miami, Fla.); Filipe, Joaquim; Cordeiro, Jose (Jose Antonio Moinhos); Pedrosa, Vitor (Berlin : Springer, 2007)
22